Addressing the achievement gap : findings and applications - Taylor, Ronald D., 1958- (Research in educational productivity., 2006)
The chapters included in this book were commissioned to serve as the background for the national invitational conference sponsored by the LSS at Temple University Center for Research in Human Development and Education (CRHDE). The conference and the publication of the conference proceedings were supported by the Institute of Education Sciences (IES) of the U. S. Department of Education. The opinions expressed do not necessarily reflect the positions of the supporting agencies and no official endorsement should be inferred.